2017
DOI: 10.18203/2320-1770.ijrcog20172328
|View full text |Cite
|
Sign up to set email alerts
|

LDH as a prognostic marker in hypertensive pregnancy

Abstract: Background: Pregnancy induced hypertension (PIH) is a global problem with a 5-15% incidence rate in India and complicating 10-17% of all pregnancies. These are multisystem disorders and lead to a lot of cellular death. LDH is an intracellular enzyme and its level is increased in these women due to cellular death. So, serum LDH levels can be used to assess the extent of cellular death and thereby the severity of disease in this group of women. The objective of the study was to correlate the severity of the dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
3
3
0
1
Order By: Relevance
“…In the present study, age of most pregnancies occurred in the age group of 20-30 years and mean age was 23.52±2.85 in all the three groups and which was similar to the studies done earlier by Talwar P et aland Mary VP et alwhere majority of the patients belonged to younger age group [8,9].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, age of most pregnancies occurred in the age group of 20-30 years and mean age was 23.52±2.85 in all the three groups and which was similar to the studies done earlier by Talwar P et aland Mary VP et alwhere majority of the patients belonged to younger age group [8,9].…”
Section: Discussionsupporting
confidence: 92%
“…4,12 Also present result supported by many studies concluded that elevated high serum LDH levels significantly correlate with the severity of preeclampsia. [13][14][15] But some studies did not find significant difference of serum LDH level between preeclamptic women and healthy pregnant women. 16,17 In the present study we found that 90% of preeclamptic women had normal levels of GGT <25 IU/L.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, CEA, CA 19-9, LDH, AMH, and HE-4 levels are not commonly increased in pregnancy and theoretically could be of additional help [7, 17, 18]. Some exceptions are inibin B, whose levels increase in the last trimester of a normal pregnancy, and LDH, which is a marker of hypertensive abnormalities related to pregnancy [19, 20].…”
Section: Diagnosis and Staging Examsmentioning
confidence: 99%
“…Surgical procedures and use of anesthetic drugs during pregnancy are considered safe [19, 20]. The benefits of either open or video biopsies for diagnostic purposes often overcome the risks and should not be withheld [7].…”
Section: Diagnosis and Staging Examsmentioning
confidence: 99%